The Effect Of Liquid Compound Fertilizers And Pruning Of Buds On The Growth And Yield Of Cherry Tomato (Lycopersicum Esculentum Mill) - M Abror; Tri Adi Kurniawan (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to determine the effect of liquid compound fertilizer and pruning of shoots on the growth and yield of cherry tomato plants. This research was conducted at green house of Muhammadiyah University of Sidoarjo from June to September 2017. This research was conducted usingfactorial ofComprehensive Random Design (CRD) and fur- ther test using BNJ test (difference real honest). The first factor was the concentration of liquid compound fertilizer consisting of 4 levels are 0%, 2%, 3% and 4%, while the second factor is pruning of buds that it consist of 2 levels, without pruning and pruning of bud. Based on the observations, there was a significant interaction between concentration of liquid compound fertilizer and pruning of budsto the heightof 28 Days After Planting and 42 Days After Planting plants, number of fruit per plant, fruit weight per plant, wet weight per plant and dry weight per plant, while on stem diameter and harvest index observation have no significant effect. The highest yield on the use of concentration of 4% compound liquid fertilizer and without pruning showed 131,33 cm of height , number of fruit per plant 10,00 pieces, weight of fruit per plant 77,73 gram , and wet weight per plant 149,98 gram.